KUALITAS PENGUNGKAPAN SUSTAINABLITY REPORT: IMPLEMENTASI CORPORATE GOVERNANCE PADA PERUSAHAAN LQ45 - Muhamad Dimas Fachriza, (2023)
This research was conducted to analyze and determine the influence of corporate governance proxied by foreign ownership, institutional ownership, expertise of the board of commissioners, the size of the board of directors and the size of the audit committee on the quality of sustainability report disclosures. This research is a quantitative study using secondary data from LQ45 companies for the 2019-2021 period. There were 25 samples of LQ45 companies for the 2019-2021 period as research samples which were then tested using the STATA 14.2 statistical application. This research resulted in that foreign ownership and institutional ownership did not have a significant influence on the quality of disclosure of sustainability reports. Then the expertise of the board of commissioners and the size of the audit committee have a significant positive influence on the quality of disclosure of sustainability reports. Meanwhile the size of the board of directors have a significant negative influence on the quality of sustainability report disclosures.